Preparing for performance: Strategies adopted across performance domains - Cotterill, S. T. (The Sport Psychologist, 2015)
The ability to prepare effectively to execute complex skills under pressure is crucial in a number of performance-focused professions. While there is emerging evidence of best practice little research has sought to compare preparation strategies across professions. As a result, the aim of this research was to explore the approaches employed within a number of professions and whether there are similarities in the techniques and strategies adopted. Participants were 18 "performers," purposefully selected from sporting, musical, performing arts, and medical domains. Participants were interviewed individually to gain an understanding of each participant`s preparation strategies and the functions these strategies fulfilled. The data were thematically analyzed using interpretative phenomenological analysis. Results suggest that there are similarities in both behavioral and mental strategies adopted across professions. Future research should seek to explore the transferability of developmental approaches.